1959
DOI: 10.1152/physrev.1959.39.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Oxygen Consumption in Man

Abstract: I 52, I 53) ; the use of Krs5 (a p-emitting isotope of krypton) as the inert gas, increasing the number of blood samples, and sampling from both internal jugular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
968
6
27

Year Published

1960
1960
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,829 publications
(1,029 citation statements)
references
References 25 publications
28
968
6
27
Order By: Relevance
“…When the Kety-Schmidt method was applied to carefully selected, elderly subjects in a clearly supe rior state of health, no age-dependent decline was found in mean CBF or mean CMR02 (Dastur et aI., 1963;Sokoloff, 1978). In more average elderly sub jects, some reduction has been found in mean CBF and mean CMR02, which is exaggerated by cerebral disease (e.g., Lassen, 1959;Dastur et a!., 1963;Ob rist, 1978;Sokoloff, 1978;Gottstein and Held, 1979;Naritomi et aI., 1979;Frackowiak et aI., 1980;Melamed et aI., 1980;Lammertsma et aI., 1981). It has been noted that the decline in mean CMRg\u is more marked than the decline in mean CBF or mean CMR02 (Dastur et aI., 1963;Gottstein et aI., 197 1;Gottstein and Held, 1979).…”
Section: Figmentioning
confidence: 99%
“…When the Kety-Schmidt method was applied to carefully selected, elderly subjects in a clearly supe rior state of health, no age-dependent decline was found in mean CBF or mean CMR02 (Dastur et aI., 1963;Sokoloff, 1978). In more average elderly sub jects, some reduction has been found in mean CBF and mean CMR02, which is exaggerated by cerebral disease (e.g., Lassen, 1959;Dastur et a!., 1963;Ob rist, 1978;Sokoloff, 1978;Gottstein and Held, 1979;Naritomi et aI., 1979;Frackowiak et aI., 1980;Melamed et aI., 1980;Lammertsma et aI., 1981). It has been noted that the decline in mean CMRg\u is more marked than the decline in mean CBF or mean CMR02 (Dastur et aI., 1963;Gottstein et aI., 197 1;Gottstein and Held, 1979).…”
Section: Figmentioning
confidence: 99%
“…Similarly, it has been shown that the incidence of adverse neurologic outcomes is increased when cerebral perfusion pressure is not maintained above the lower limit of cerebral autoregulation (LLA) 2. The LLA is defined as the pressure below which blood flow in the brain becomes pressure dependent, and is often assumed to be a mean arterial blood pressure (MAP) of 50 mm Hg 3. However, previous studies by our group have questioned this assumption and demonstrated that during surgery and anesthesia, the range for the LLA varies considerably between 40 and 90 mm Hg 4.…”
Section: Introductionmentioning
confidence: 99%
“…As blood gases were not altered after TRH administration, this reduction in pH may reflect the dissociation of tartaric acid from its complex with TRH. The intravascular in jection of a low pH solution does not result in CBF changes if P aco2 is maintained constantly and if the blood-brain barrier remains intact (Lassen, 1959;Harper and Bell, 1963). Thus, this slight decrease in pH is not considered to be responsible for the in crease of CBF after TRH administration.…”
Section: Discussionmentioning
confidence: 99%